Comparing the accuracy of default predictions in the rating industry: The case of Moody's vs. S&P - Walter Krämer; André Güttler (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
We consider 1927 borrowers from 54 countries who had a credit rating by both Moody's and S&P as of the end of 1998, and their subsequent default history up to the end of 2002. Viewing bond ratings as predicted probabilities of default, we show that it is unlikely that both agencies are well calibrated, and that the ranking of the agencies depends crucially on the way in which probability predictions are compared.
Keywords: 519; credit rating; probability forecasts; calibration; Kreditwürdigkeit; Konkurs; Prognoseverfahren; Kreditrisiko; Vergleich; USA; Welt